2005
DOI: 10.1111/j.1467-8624.2005.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Peer Victimization and Perceptions of the Self and Schoolmates: Precursors to Internalizing and Externalizing Problems

Abstract: Evidence indicates that peer victimization is predictive of later maladjustment, but the mechanisms by which harassment impairs development have yet to be identified. The objectives of this study were (a) to discern normative trends in peer victimization experiences and self- and peer perceptions during preadolescence and (b) to investigate associations between individual differences in these trajectories and changes in psychosocial adjustment. A sample of 381 children (196 girls; 185 boys) was followed longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
235
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(270 citation statements)
references
References 88 publications
25
235
2
5
Order By: Relevance
“…Overall, the observed trajectory patterns are in line with studies showing that, on average, peer victimization decreases over the course of middle childhood and into mid-adolescence (Reavis et al, 2010;Troop-Gordon & Ladd, 2005). These findings are encouraging, as they suggest that -in most cases -the transition to secondary school offers the chance to escape previous suffering.…”
Section: Strengths Limitations and Conclusionsupporting
confidence: 86%
“…Overall, the observed trajectory patterns are in line with studies showing that, on average, peer victimization decreases over the course of middle childhood and into mid-adolescence (Reavis et al, 2010;Troop-Gordon & Ladd, 2005). These findings are encouraging, as they suggest that -in most cases -the transition to secondary school offers the chance to escape previous suffering.…”
Section: Strengths Limitations and Conclusionsupporting
confidence: 86%
“…It has been suggested that low-status positions in peer groups may cause children to have a diminished sense of belonging and relatedness to others (Baumeister and Leary 1995), which may increase the risk of depression. Indeed, it was found that children who are victimized tend to have increased levels of loneliness (Troop-Gordon and Ladd 2005), and decreased social satisfaction (Kochenderfer-Ladd and Wardrop 2001) compared to others. Moreover, children who are victimized may attribute victimization to their own deficiencies, potentially compromising their self-worth and precipitating depressive symptoms (Ladd and Troop-Gordon 2003;Troop-Gordon and Ladd 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that children who are victimized tend to have increased levels of loneliness (Troop-Gordon and Ladd 2005), and decreased social satisfaction (Kochenderfer-Ladd and Wardrop 2001) compared to others. Moreover, children who are victimized may attribute victimization to their own deficiencies, potentially compromising their self-worth and precipitating depressive symptoms (Ladd and Troop-Gordon 2003;Troop-Gordon and Ladd 2005). Additionally, it has been shown that children who are depressed are more likely to be victimized (Kochel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the wealth of empirical research that exists concerning specific mental health problems and links with violent crime and delinquency, it is striking that the majority of developmental studies examine only one or two clinical levels or types of mental disorder at a time (e.g., Conduct Disorder (CD) and Oppositional Defiant Disorder) or, conversely, focus on groups of mental health problems under a larger categorical framework (e.g., mood disorders or disruptive disorders), but ignoring the influence of other co-occurring mental health disorders that may also be related to antisocial behaviors. Alternatively, another empirical body of research has utilized internalizing or externalizing constructs of related mental health symptoms to group psychopathological problems by their common features, in an effort to study the link between psychopathology and violence [see e.g., Bardick and Bernes, 2008;Dennis et al, 2006;Troop-Gordon and Ladd, 2005].…”
Section: Introductionmentioning
confidence: 99%